Baseline levels of low-density lipoprotein cholesterol and lipoprotein (a) and the AvaII polymorphism of the low-density lipoprotein receptor gene influence the response of low-density lipoprotein cholesterol to pravastatin treatment - Lahoz, Carlos; Peña, Rocío; Mostaza, Jose M.; Laguna, Fernando; García-Iglesias, María F.; Taboada, Manuel; Pintó, Xavier (Metabolism, clinical and experimental, 2005)
To investigate some individual and genetic factors that may influence the response of low-density lipoprotein cholesterol (LDL-C) to pravastatin treatment, we recruited 440 subjects with hypercholesterolemia (mean age, 57 years; 43% men) from 21 primary health care centers-outpatient clinics into a prospective, multicentered intervention trial. Pravastatin (20 mg/d) was prescribed for 16 weeks. The main outcome was the percentage variation in LDL-C concentration relative to baseline. Blood analyses and genotyping were performed centrally. The results indicated that LDL-C decreased by 20.5% (range, +21% to −66%) after pravastatin treatment. Baseline concentration of LDL-C (the higher the concentration, the greater the decrease), lipoprotein (a) levels (the lower the concentration, the greater the response), and AvaII polymorphism of the LDL-receptor gene significantly influenced the hypolipemic effect ( P < .001, P = .014, and P = .004, respectively). These 3 factors combined explained 10.6% of the variation in LDL-C response. Age, sex, smoking habit, alcohol consumption, body mass index, and apolipoprotein E genotype had no significant effect on response. We conclude that baseline levels of LDL-C and lipoprotein (a) together with the AvaII polymorphism of the LDL-receptor gene have a significant influence on the LDL-C response to pravastatin treatment in patients monitored in a standard primary health care outpatient clinic setting.